The Impact of Working Motivation and Working Environment on Employees Performance in Indonesia Stock Exchange - Riyanto, Setyo; Sutrisno, Ady; Ali, Hapzi (International Review of Management and Marketing, 2017)
In the face of the Asean economic community role of capital market demanded to be pro-active. The capital market expected to have contribution to the Indonesian economy by preparing regulations in accordance with the actual of economic conditions which would require of human resources who has a good performance at Indonesia stock exchange (IDX) as the regulator of capital market in Indonesia. This research aims to know the influence of working motivation toward employee performance at IDX, to know the influence of working environment toward employee performance at IDX and to know the influence of working motivation and working environment toward employee performance in IDX. The research design was descriptive and verification with survey method. The population all employees of IDX in Jakarta. The sampling technique based on the calculation Slovin found 150 respondents with a probability sampling with the type of simple random sampling. Data analyzed using multiple linear regression analysis. The results showed that there is a simultaneous effect on working motivation and working environment on employee performance. Working motivation and working environment partially significant influence on employee performance. Suggestion for IDX can provide good motivation and give more attention and achievement for employees as well as providing a working environment that can support employee performance. Keywords: Working Motivation, Working Environment, Employee Performance JEL Classifications: M52, M53, M54